2018
DOI: 10.1002/ange.201800705
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Active N‐Heterocyclic Carbene Manganese(I) Complex for Selective Electrocatalytic CO2 Reduction to CO

Abstract: We report here the first purely organometallic fac-[Mn I (CO) 3 (bis-Me NHC)Br] complex with unprecedented activity for the selective electrocatalytic reduction of CO 2 to CO,e xceeding 100 turnovers with excellent faradaic yields (h CO % 95 %) in anhydrous CH 3 CN.U nder the same conditions,amaximum turnover frequency (TOF max )of2100 s À1 was measured by cyclic voltammetry,w hichc learly exceeds the values reported for other manganese-based catalysts.M oreover,t he addition of water leads to the highest TOF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Aside from that, well-designed molecular metal complexes were developed to reduce CO 2 . In this regard, some molecular Mn-complexes like Mn(bipyridine)-pyrene, [9] N-heterocyclic carbene Mn I complex [10] and other similar complexes immobilized over supports like multi-walledcarbon-nanotubes (MWCNT) [11] or Nafion membrane [12] have been reported to reduce CO 2 to CO. Recently, we have observed that a cobalt(III) triphenylphosphine corrole complex exhibits potential dependent CO 2 reduction at pH 6 to produce methanol, ethanol, and low amounts of acetic acid (FE max.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from that, well-designed molecular metal complexes were developed to reduce CO 2 . In this regard, some molecular Mn-complexes like Mn(bipyridine)-pyrene, [9] N-heterocyclic carbene Mn I complex [10] and other similar complexes immobilized over supports like multi-walledcarbon-nanotubes (MWCNT) [11] or Nafion membrane [12] have been reported to reduce CO 2 to CO. Recently, we have observed that a cobalt(III) triphenylphosphine corrole complex exhibits potential dependent CO 2 reduction at pH 6 to produce methanol, ethanol, and low amounts of acetic acid (FE max.…”
Section: Introductionmentioning
confidence: 99%
“…61 Evidence for the production of CO3 2− is obtained in the SEC-IR experiments. This was also the proposed mechanism for the purely organometallic manganese catalyst IV (Scheme 1) described above 29 and for (2'2-bipyridine)Re(CO)3Cl, which also catalyzes the CO2-to-CO/CO3 2conversion. In the latter case, a dimeric rhenium species was postulated as crucial intermediate.…”
Section: Figurementioning
confidence: 56%
“…At the onset of the catalytic wave (Figure 4, red), bands at frequencies of 1685 and 1645 cm −1 appear which are characteristic for HCO3 − and CO3 2− . 29 Under catalytic conditions no Fe 0 species is observed by SEC-IR and [LFe I (CO)] + represents the steady state species. When the potential is scanned beyond the catalytic wave, the current decreases indicating that CO2 is consumed, the baseline of the IR spectra shifts, reflecting the evolution of CO gas, (Figure 4, blue).…”
Section: Figurementioning
confidence: 97%
See 2 more Smart Citations